Burden of depression and anxiety among leprosy affected and associated factors-A cross sectional study from India. - Karthikeyan Govindasamy; Immanuel Jacob; Raju Moturu Solomon; Joydeepa Darlong (Public Library of Science (PLoS), 2021)
Background Leprosy is a Neglected Tropical Diseases (NTDs) known to cause stigma and discrimination in low-and middle-income countries. It often results in visible impairments, thus pre-disposing to poor mental health. Aim of the study was to estimate the prevalence of depression and anxiety among people affected by Leprosy and to determine the associated factors. Methodology/principal findings A multi-centric, cross-sectional study was carried out in four leprosy endemic states of India-Chhattisgarh, Maharashtra, West Bengal and Tamil Nadu in randomly selected blocks (a sub-unit of district), from one district in each state. From selected blocks those registered for leprosy treatment at public health or referral centres, people above the age of 18 years were interviewed with PHQ-9 and GAD-7 questionnaires for Depression and Anxiety, respectively. Disease profile like leprosy classification, deformity grade, number and site of the patches and socio-economic status were collected along with individual data. Of the total 220 respondents, prevalence of depression and anxiety symptoms was, 33% (73) and 19% (42), respectively. Presence of disability (47%) and Female gender (46%) were significantly associated with depression. Presence of disability (32%), Lower income group (27%) and low education (22%) were significantly associated with symptoms of anxiety. As the severity of disability increased, risk of developing depression and anxiety increased. Conclusion The study indicates that more than 30% of people affected by leprosy have mental health problems, which emphasizes the importance of mental health care services in leprosy. Women, those who had lower level of education, those belonging to lower socio-economic status and those with any level of disability due to leprosy are at risk of developing depression and/or anxiety. The study concludes more attention to be paid to the categories identified to be at risk.